2015
DOI: 10.1155/2015/754562
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Teaching-Learning-Based Optimization with Differential Learning and Its Application

Abstract: The teaching-learning-based optimization (TLBO) algorithm is a population-based optimization algorithm which is based on the effect of the influence of a teacher on the output of learners in a class. A variant of teaching-learning-based optimization (TLBO) algorithm with differential learning (DLTLBO) is proposed in the paper. In this method, DLTLBO utilizes a learning strategy based on neighborhood search of teacher phase in the standard TLBO to generate a new mutation vector, while utilizing a differential l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It is also noteworthy that the strategy of assigning same mean position that represents the mainstream knowledge of population for all learners is contradictory with real-world scenario of teaching and learning because each learner supposed to have slightly different perception on the mainstream knowledge of classroom [42]. In addition, it is observed that the learner phases of some TLBO variants [9,10,15,16,19,20,23,30,[36][37][38][39] did not accurately reflect the actual scenario of peer interaction in classroom. Some of these TLBO variants also only allowed each learner to interact with same peer learner in all dimensions during the learner phase.…”
Section: B Challenges Of Existing Workmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also noteworthy that the strategy of assigning same mean position that represents the mainstream knowledge of population for all learners is contradictory with real-world scenario of teaching and learning because each learner supposed to have slightly different perception on the mainstream knowledge of classroom [42]. In addition, it is observed that the learner phases of some TLBO variants [9,10,15,16,19,20,23,30,[36][37][38][39] did not accurately reflect the actual scenario of peer interaction in classroom. Some of these TLBO variants also only allowed each learner to interact with same peer learner in all dimensions during the learner phase.…”
Section: B Challenges Of Existing Workmentioning
confidence: 97%
“…In [15], differential learning TLBO (DLTLBO) was proposed to search for the optimal parameters of digital infinite impulse response filter. It was leveraged by interactive learning strategies designed in teacher phase.…”
Section: ) Single Objective Optimizationmentioning
confidence: 99%
“…Huang et al [30] proposed an effective teaching-learning-based cuckoo search (TLCS) algorithm for parameter optimization problems in structure designing and machining processes. Zou et al [31] proposed an improved teaching-learning-based optimization with differential learning (DLTLBO) for IIR System Identification problems. Wang et al [32] combined TLBO with differential evolution to propose TLBO-DE for chaotic time series prediction.…”
Section: Improvements On Tlbomentioning
confidence: 99%
“…(i) Basic TLBO [11] (ii) Modified TLBO (mTLBO) [23] (iii) Differential learning TLBO (DLTLBO) [31] (iv) Nonlinear inertia weighted TLBO (NIWTLBO) [22] (v) TLBO with learning experience of other learners (LETLBO) [24] (vi) Generalized oppositional TLBO (GOTLBO) [44] Table 1 lists the parameter settings for LebTLBO and the other TLBO algorithms. Table 2 shows the mean error and standard deviation (in bracket) of the function error values obtained by all the TLBO algorithms.…”
Section: Comparison With Other Tlbo Algorithmsmentioning
confidence: 99%
“…One of the most important issues is that the population tends to be trapped in the local optima solution because of diversity loss. To improve the performance of the original TLBO, a few modified or improved algorithms are proposed in recent years, such as teaching-learning-based optimization with dynamic group strategy (DGSTLBO) [20], teaching-learning-based optimization with neighborhood search (NSTLBO) [21], an elitist teaching-learning-based optimization algorithm (ETLBO) [22], and a variant of teaching-learning-based optimization algorithm with differential learning (DLTLBO) [23]. These modified TLBOs have better performance than the original TLBO on classical benchmark functions.…”
Section: Introductionmentioning
confidence: 99%